Taxonomy of the genus Bolitogyrus Chevrolat (Coleoptera: Staphylinidae: Staphylinini: Quediina) from China with description of seven new species - Cai, Yan-Peng; Zhao, Zong-Yi; Zhou, Hong-Zhang (Zootaxa, 2015)
Seven new species of the genus Bolitogyrus Chevrolat, 1842 are described based on specimens collected in China, namely B. depressus sp. nov. from Guangdong, B. hainanensis sp. nov. and B. magnimaculosus sp. nov. from Hainan, B. metallicus sp. nov. from Hubei, and B. loculus sp. nov., B. profundus sp. nov. and B. uncus sp. nov. from Yunnan. The number of Bolitogyrus species is thus increased to 59. Line drawings and color illustrations of adults and genitalia of the new species and some others are given. A key to species known from China is provided, with the exception of B. fukienensis Scheerpeltz, 1974, which is only known from females. A geographical distribution map of all Chinese species is also compiled.